Pengaruh Exposure Time dan Postur Tubuh untuk Mengurangi Cybersickness dengan Indikator Konduktansi Kulit dalam Penggunaan Virtual Reality - Graziella, Ivana; Theresia, Clara (Jurnal Rekayasa Sistem Industri, 2025)
Cybersickness is a nausea, dizziness, and losing balance while using VR. Cybersickness is caused by exposure time and the body posture of the VR’s user that until now there are still differences in research results regarding the effects on cybersickness. Therefore, this study aims to identify the effects on cybersickness and provide appropriate recommendations to reduce cybersickness symptoms. The measurement of research were Galvanic Skin Response as an objective indicator and the Simulator Sickness Questionnaire (SSQ) questionnaire as a subjective indicator. A total of 48 participants will be given the task of playing parkour activities with sitting or standing postures and played for 10 minutes, 20 minutes, or 30 minutes. To determine the effect of exposure time and body posture, were used ANOVA test and the Kruskal-Wallis test. Based on the results, exposure time has an effect on with the maximum effect at 20 minutes which has an average SSQ value of 109,863 (p-value = 0,046 < 0,05). Meanwhile, body posture also affects cybersickness which standing posture has a higher average GSR (13,082 μS) and p-value = 0,002 < 0,05. The recommendations which are given are the duration using VR is no more than 20 minutes and maintain a balanced body posture which can move their heads slowly to so that the level of cybersickness can be reduced.